Portraits of English Language Teachers from the Symbolic Meaning of “The Allegory of the Cave” of Plato in the Context of Vietnam: Insiders’ Perspectives - Phan, Thi Tuyet Van; Nguyen, Duy Khang (Pedagogika Społeczna Nova, 2025)
By the symbolic meaning of “The Allegory of the Cave” as a theory of how humans gained knowledge, Plato meant to imply the limitations in human perception when interacting with the real world. A close relationship between this theory and English teaching in the context of Vietnam was seen from the connotation with complete reflection on the drawbacks of the reality of teaching English at high schools, colleges, and universities for non-English major students. A survey was conducted with data collection from some high school, college, and university teachers to gain more evidence for the situation. The educational stakeholders were also involved in this study to consolidate the viewpoints. The study applied critical pedagogy from some of the most influential proponents in the world to deal with problems. The research results showed that teachers were still under the influence of traditional education and cared much about transmitting as much knowledge as possible to the learners. However, they also expected to change the situation with a number of recognitions and criticism. It was suggested that teachers should get out of their comfort zone and change for the better in teaching and learning English, and the nature of education should be identified differently.